(untitled) (Journal on studies and research of academic knowledge, 2019)
The human factor is a relevant element of competitiveness, but in smaller companies, it is not common to give priority to this valuable resource. The objective of the study is to analyze the importance of human talent management for the competitiveness of Commercial MSMEs in the Natalio and Yatytay districts. Through the documentary review, the topics of human talent management processes and the determining factors of business competitiveness are addressed. The qualitative methodology allows an interpretative analysis of the results of the interviews applied to the managers / owners of the Commercial MSMEs of the districts mentioned above. Among the characteristics of this type of company, it is found that there is practically no organizational culture, which leads to a totally rudimentary human talent management system, where most of the workers are members of their own family. While, from a competitive point of view, the regular use of technologies, little innovation, scarce commercial strategies, and of course, the almost null management of human talent stand out. There is potential in human talent, however, they are not being well taken advantage of due to deficiencies in the management processes, which leads to low competitiveness of companies for a broader and long-term market, businesses have limited growth, so they end up staying a long time in the classification of micro business, without being able to pass to small or medium.